2020
DOI: 10.7762/cnr.2020.9.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Diets and Schizophrenia

Abstract: Schizophrenia is a mental illness characterized by symptoms such as hallucinations, delusions, disorganized speech, disorganized or catatonic behavior, and negative symptoms (emotional flatness, apathy, and lack of speech). It causes social and economic burdens to patients and their family. Although etiology of schizophrenia is still uncertain, dopamine dysregulation is traditionally considered as a main etiological factor of schizophrenia, which has been utilized to develop drugs for treating schizophrenia. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 99 publications
(76 reference statements)
2
11
0
Order By: Relevance
“…Gut dysbiosis has been reported in persons with schizophrenia, with reports that increase in the Succinivibrio and Corynebacterium bacterial genera exacerbated schizophrenia symptom severity[ 73 ]. Gut dysbiosis also increases susceptibility to infections and inflammation[ 74 ]. However, direct proof that diet-induced change in gut microbiota may be a direct cause of schizophrenia symptoms is harder to obtain.…”
Section: Nutrition In Mental Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Gut dysbiosis has been reported in persons with schizophrenia, with reports that increase in the Succinivibrio and Corynebacterium bacterial genera exacerbated schizophrenia symptom severity[ 73 ]. Gut dysbiosis also increases susceptibility to infections and inflammation[ 74 ]. However, direct proof that diet-induced change in gut microbiota may be a direct cause of schizophrenia symptoms is harder to obtain.…”
Section: Nutrition In Mental Health and Diseasementioning
confidence: 99%
“…Studies have reported that diets that are low in anti-inflammatory or rich in pro-inflammatory factors (omega-6 fatty acids are pro-inflammatory in contrast to omega-3 fatty acids that are anti-inflammatory) activate or worsen neuroinflammation, and if left uncontrolled, can induce pathologic changes of schizophrenia and exacerbate schizophrenia symptom severity[ 74 , 76 ]. Exposure to diets rich in gluten has been associated with an increase in the expression of human leukocyte antigen markers, which increase cells susceptible to attacks by T-cells, allowing the release of pro-inflammatory cytokines.…”
Section: Nutrition In Mental Health and Diseasementioning
confidence: 99%
“…By contrast, although clinical trials have not yet evaluated the beneficial impact of the Mediterranean diet or other healthy life-style factors for SZ, some researchers hypothesize that they could improve metabolic and other disease outcomes related to premature mortality in SZ (159). Some nutritional deficiencies have been proposed to play a role in the etiopathogenic mechanisms of SZ, and particular dietary interventions have been proposed to reverse the SZassociated neurobiological changes established in the early phases, at least for certain cohorts of SZ patients (160). Regarding nutritional deficiencies, evidence has shown that PUFAs deficits are associated with both negative and positive symptoms of SZ.…”
Section: Gut Microbiota Diet and Schizophreniamentioning
confidence: 99%
“…Some nutritional deficiencies have been proposed to play a role in the etiopathogenic mechanisms of SZ, and particular dietary interventions have been proposed to reverse the SZ-associated neurobiological changes established in the early phases, at least for certain cohorts of SZ patients ( 160 ). Regarding nutritional deficiencies, evidence has shown that PUFAs deficits are associated with both negative and positive symptoms of SZ.…”
Section: Gut Microbiota Diet and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation